Evaluation of the Performance of Females as Light Infantry Soldiers. (18th August 2014) - Finestone, Aharon S.; Milgrom, Charles; Yanovich, Ran; Evans, Rachel; Constantini, Naama; Moran, Daniel S.
Abstract : A few countries permit women to serve in combat roles, but their long term performance in these positions has not been reported. The incidences of overuse injuries and attrition of 85 male and 235 female recruits in a light infantry brigade was followed in a three-year prospective study. Females were shorter (162 cm, CI 161–163 cm) than males (174 cm, CI 173–176), had more body fat (18.9 kg, CI 18.2–19.6 kg) than males (12.6 kg, 11.3–13.8 kg), had lower V ˙ O2 max (36.8 mL·min −1 ·kg −1, CI 35.8–37.78 mL·min −1 ·kg −1 ) than males (50.48 mL·min −1 ·kg −1, CI 48.4 to 52.48 mL·min −1 ·kg −1 ), had more stress fractures (21.0%, 95% CI 16.2–26.5%) than males (2.3%, CI 0.3–8.2%), and had more anterior knee pain (41.2%, CI 34.9–47.7%) than males (24.7%, CI 16.0–35.2%). Three-year attrition was 28% CI 22–34% for females and 37% CI 26–48% for males. The females in this study successfully served as light infantry soldiers. Their lower fitness and high incidence of overuse injuries might impede service as regular infantry soldiers.